Analysis of the Impact of Covid-19 on the Municipal Markets of Lima Cercado 2020 (Revista Científica Interdisciplinaria Investigación y Saberes, 2021)
The activities of the markets were affected by the pandemic; the research "Analysis of the impact of Covid-19 in the municipal markets of Lima Cercado, 2020" had as objective, to explain theimpact of Covid-19 in the municipal markets; where the study was focused and applied the actions and sanitary measures that were decreed and implemented by the national government before the state of national sanitary emergency; promoting its compliance by the traders and the population in general. The methodology was a basic type of study, with a qualitative approach; the research design was the case study; the traders of the Ramón Castilla municipal market, officials, professionals, technicians of the Municipality of Lima and the user public participated in the interview; for the analysis, data triangulation was used. The results showed that the emergency sanitary actions and measures were effective, despite the fact that small groups showed reluctance and resistance to this change. He concluded that the sanitary actions and measures partially helped to contain the spread of Covid-19; the most outstanding aspect was the coordination between the merchants and the municipal administration, allowing tolerance and teamwork with responsible and positive attitudes.